Interior design marketing strategy using SWOT analysis - Nuraida Wahyuni; Shanti Kirana Anggraeni; Gilang Restu Saepudin (Universitas Sultan Ageng Tirtayasa, 2022)
The Covid pandemic has been successfully overcome. Estimates of the weak world economy have also been predicted. However, it is noted that the need for housing continues to increase. Along with the increasing need for residential homes, interior design services also increased. This increase is because people need a comfortable place to live. Especially with the house offering a limited area, a compact interior design is needed. Therefore, the offer of interior design services is increasingly widespread. Warna Dipa, as one of the interior service providers, requires a marketing strategy for the company to compete with its competitors. This study aimed to obtain a marketing strategy for Warna Dipa using a SWOT analysis. This study performed direct observation on the ground and interviews with the management of Warna Dipa to collect the data. The data was collected from internal and external factors of the company. The results show tactical and development strategies for Warna Dipa. Tactical strategies include using social media to expand marketing reach, collaborate with furniture providers, and increase product prototypes.